Ultrahigh-loading-capacity copper monatomic catalyst, preparation method thereof and acetylene semi-hydrogenation application of ultrahigh-loading-capacity copper monatomic catalyst

By preparing high-loaded copper single-atom catalysts, the problem of insufficient loading of copper-based single-atom catalysts in the prior art is solved, and efficient acetylene reduction catalysis is achieved, ethylene purity and atom utilization rate are improved, and cost is reduced. .

CN119186622AActive Publication Date: 2024-12-27XI AN JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411461827.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-27
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Existing copper-based single-atom catalysts are difficult to achieve high loading and cannot meet the needs of industrial ethylene preparation and acetylene removal. In addition, traditional thermal catalytic processes consume high energy and cost.

Method used

The polymer carbon nitride was obtained by calcining the nitrogen-containing precursor, mixing it with the copper precursor, and then ultrasonic and drying it. The high-load-loaded copper single-atom catalyst was prepared by vacuum calcining, which was used for electrocatalyzing the acetylene reduction reaction.

Benefits of technology

The preparation of a high-load copper single-atom catalyst has excellent catalytic properties, can efficiently catalyze acetylene reduction, improve the purity and atomic utilization of ethylene and reduce costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186622A_ABST
    Figure CN119186622A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrahigh-loading copper monatomic catalyst, a preparation method thereof and an acetylene semi-hydrogenation application of the ultrahigh-loading copper monatomic catalyst, and the preparation method comprises the following steps: roasting a nitrogen-containing precursor to obtain polymer carbon nitride; the preparation method comprises the following steps: adding polymer carbon nitride into an ethanol dispersion liquid of a copper precursor, carrying out ultrasonic treatment to obtain a mixed material liquid, and evaporating to obtain powder; and roasting the powder in vacuum to obtain the high-loading-capacity supported copper monatomic catalyst. The prepared copper monatomic catalyst is used for electrocatalytic acetylene reduction reaction, the catalyst with the optimal material loading component can catalyze C2H2 to C2H4 with high selectivity (the highest C2H4 Faraday efficiency is greater than 98%), and atomic-scale dispersed metal sites inhibit carbon-carbon coupling in the reaction; the Faraday efficiency of butadiene in a test total current range can be reduced to 0.5% or below, and the catalyst shows excellent catalytic activity and stability in an electro-catalytic acetylene hydrogenation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst preparation, and more specifically, relates to an ultra-high-load copper single-atom catalyst, a preparation method thereof, and an application in acetylene semi-hydrogenation. Background Art

[0002] Ethylene is a very important chemical raw material and an important commodity raw material for the production of polymers such as polyethylene. However, the industrial production of ethylene will inevitably produce about 0.5-3% acetylene. This small amount of acetylene will quickly poison the Ziegler-Natta polymerization catalyst during the olefin polymerization process, greatly reducing the target polymer yield. Therefore, it is particularly important to purify industrial ethylene and remove acetylene impurities. Currently, this goal is mainly achieved through thermal catalytic hydrogenation of acetylene, but the reaction usually needs to be carried out at higher temperatures and pressures (~200°C, ~5 bar); in addition, the large consumption of hydrogen and the high price of palladium-based catalytic materials also increase the application cost of the reaction. The electrochemical acetylene reduction process driven by clean renewable energy is green and low-energy. Using water as a proton source can avoid the participation of excessive hydrogen and is expected to replace the traditional thermal catalytic process. Copper single-atom catalysts have been widely used due to their low cost and high atomic utilization rate, but existing copper-based single-atom catalysts are difficult to achieve high loading and cannot meet application requirements. Summary of the invention

[0003] In order to solve the problem in the prior art that it is difficult for copper-based single-atom catalysts to achieve high loading, the purpose of the present invention is to provide an ultra-high loading copper single-atom catalyst and a preparation method and application of acetylene semi-hydrogenation, wherein the single-atom catalyst has a high loading and has excellent catalytic performance in the electrocatalytic acetylene reduction reaction.

[0004] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing an ultra-high loading supported copper single atom catalyst comprises the following steps: calcining the nitrogen-containing precursor to obtain polymer carbon nitride; Adding polymer carbon nitride to an ethanol dispersion of a copper precursor, ultrasonicating to obtain a mixed liquid, and evaporating to obtain a powder; The powder is calcined under vacuum to obtain a high-load supported copper single-atom catalyst.

[0005] A further improvement of the present invention is that the nitrogen-containing precursor is dicyandiamide or melamine.

[0006] A further improvement of the present invention is that the calcination conditions of the nitrogen-containing precursor are: first calcination at 550-560° C. for 1-3 h, then calcination at 500-510° C. for 5-7 h, and repeating calcination at 500-510° C. for 5-7 h 3-4 times.

[0007] A further improvement of the present invention is that the temperature is 1-3°C·min -1 The heating rate is 4-6℃·min -1 The heating rate is increased to 500-510°C.

[0008] A further improvement of the present invention is that the mass ratio of polymer carbon nitride to copper precursor is 0.05:0.0082-0.0571.

[0009] A further improvement of the present invention is that the copper precursor is 1,5-cyclooctadiene copper chloride dimer or copper chloride.

[0010] A further improvement of the present invention is that the powder is calcined under vacuum at a temperature of 450-460° C. for a time of 1-2 hours.

[0011] A further improvement of the present invention is that at 5°C·min -1 The heating rate is increased to 450-460°C.

[0012] An ultra-high loading supported copper single atom catalyst.

[0013] Application of an ultra-high loading supported copper single atom catalyst in the electrocatalytic acetylene reduction reaction.

[0014] The present invention provides the use of the supported copper single-atom catalyst described in the above scheme in the electrocatalytic acetylene reduction reaction.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention obtains polymer carbon nitride by calcining a nitrogen-containing precursor, and then mixes it with a copper precursor, ultrasonicates it, dries it, obtains a powder, and then calcines it to obtain a high-loaded copper single-atom catalyst. The raw material source is wide and easy to implement. The copper single-atom catalyst prepared by the present invention is used for the electrocatalytic acetylene reduction reaction. The catalyst with the optimal material loading component can catalyze C2H2→C2H4 with high selectivity (the highest C2H4 Faraday efficiency can reach>98%), and the atomic-level dispersed metal sites inhibit the carbon-carbon coupling in the reaction. The Faraday efficiency of butadiene can be reduced to less than 0.5% within the full current range of the test. Compared with the current nano-scale copper-based catalyst (the Faraday efficiency of butadiene is generally 3%-10%), the generation of butadiene in the process of ethylene preparation and crude ethylene impurity removal is greatly reduced, the purity of the target product ethylene is improved, and the subsequent ethylene processing and utilization process is facilitated, the atomic utilization rate is greatly improved, and the cost is saved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the X-ray powder diffraction pattern (XRD) of the catalyst prepared in Example 1-5; Figure 2 is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of the catalyst prepared in Example 3; Figure 3 The X-ray absorption fine structure (EXAFS) spectra of the catalysts prepared in Examples 1-5; Figure 4 The catalyst prepared in Example 1-5 was -2 Faraday efficiency distribution diagram under constant current test; Figure 5 The Faraday efficiency distribution diagram of the catalyst prepared in Example 3 at different current densities using a flow cell as an electrolytic cell; Figure 6 This is a graph showing the impurity removal data of the catalyst prepared in Example 3 using a membrane electrode as an electrolytic cell in a crude ethylene gas stream containing acetylene impurities. DETAILED DESCRIPTION

[0017] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0018] A method for preparing an ultra-high loading supported copper single atom catalyst of the present invention comprises the following steps: S1: calcining a nitrogen-containing precursor to obtain a carrier polymer carbon nitride; wherein the nitrogen-containing precursor includes but is not limited to dicyandiamide or melamine. The calcination is divided into multiple steps, the first step of which is calcined at a temperature of 550-560°C, for 1-3 hours, and at a heating rate of 1-3°C·min -1 The second step is calcination at 500-510℃, time 5-7h, heating rate 4-6℃·min -1 Repeat the second step of calcination 3-4 times until the polymer carbon nitride turns white. After multiple calcinations, the polymer carbon nitride support can be transformed from block to nanosheet by simple thermal stripping, increasing the specific surface area of ​​the catalyst and providing more sites for loading metals.

[0019] S2: Dispersing the copper precursor in anhydrous ethanol and fully sonicating for 10 to 30 minutes to obtain a dispersion A; wherein the copper precursor includes but is not limited to 1,5-cyclooctadiene copper chloride dimer or copper chloride.

[0020] S3: Add the carrier prepared in S1 to the dispersion A and perform sufficient ultrasonication, and perform rotary evaporation on the obtained mixed liquid to obtain a powder; wherein the rotary evaporation temperature is preferably 50°C and the rotation speed is 130rpm. The present invention has no special requirements on the time of the rotary evaporation, and the liquid in the mixed liquid can be evaporated to dryness.

[0021] S4: Put the powder obtained in step S3 into the raw material end of the bottom of the single-ended quartz tube, and use a vacuum tube sealing machine to evacuate the air so that the air pressure in the tube drops to 10 -4 Pa, and then use the hydrogen-oxygen machine to seal the tube; S5: calcining to obtain a high-load supported copper single-atom catalyst, wherein the calcination temperature is 450-460°C, the time is 1-2h, and the heating rate is 5°C·min -1 .

[0022] The ultra-high-load supported copper single-atom catalyst prepared in the present invention comprises a carrier and copper single atoms supported on the carrier, wherein the mass of the copper single atoms is 5-35% of the mass of the catalyst.

[0023] The ultra-high loading supported copper single atom catalyst prepared in the present invention can be used for electrocatalytic acetylene reduction reaction.

[0024] The following are specific embodiments.

[0025] Example 1 The nitrogen-containing precursor is calcined to obtain a carrier polymer carbon nitride; wherein the nitrogen-containing precursor is dicyandiamide. The calcination is divided into multiple steps, and the first step is calcined at a temperature of 550°C, for 2 hours, and at a heating rate of 2.3°C·min -1 The second step calcination temperature is 500℃, the time is 5h, and the heating rate is 5℃·min-1 Repeat the second step of calcination three times until the polymer carbon nitride turns white.

[0026] 0.0082 g of 1,5-cyclooctadiene copper chloride dimer and 30 mL of anhydrous ethanol were placed in a 150 mL eggplant-shaped bottle, and mixed by ultrasonication for 10 min. Then, 0.0500 g of polymer carbon nitride carrier was added, and ultrasonication was performed for 20 min to obtain a mixed liquid. The mixed liquid was rotary evaporated at a rotary evaporation temperature of 50° C. and a rotation speed of 130 rpm to obtain a powder. The obtained powder was placed in the raw material end at the bottom of a single-ended quartz tube, and the air pressure in the quartz tube was reduced to 10 by a vacuum tube sealing machine. -4 Pa, and then use the hydrogen-oxygen machine to seal the tube; put the quartz tube into the tube furnace and heat it at 5℃·min -1 The heating rate was increased to 450°C and calcined for 1 hour to obtain a copper single atom catalyst with a mass content of 5wt% supported on a polymer carbon nitride substrate.

[0027] Example 2 The nitrogen-containing precursor is calcined to obtain a carrier polymer carbon nitride; wherein the nitrogen-containing precursor is dicyandiamide. The calcination is divided into multiple steps, and the first step is calcined at a temperature of 550°C, for 2 hours, and at a heating rate of 2.3°C·min -1 The second step calcination temperature is 500℃, the time is 5h, and the heating rate is 5℃·min -1 Repeat the second step of calcination three times until the polymer carbon nitride turns white.

[0028] 0.0245 g of 1,5-cyclooctadiene copper chloride dimer and 30 mL of anhydrous ethanol were placed in a 150 mL eggplant-shaped bottle, and mixed by ultrasonication for 10 min. Then, 0.0500 g of polymer carbon nitride carrier was added, and ultrasonication was performed for 20 min to obtain a mixed liquid. The mixed liquid was rotary evaporated at a rotary evaporation temperature of 50° C. and a rotation speed of 130 rpm to obtain a powder. The obtained powder was placed in the raw material end at the bottom of a single-ended quartz tube, and the air was evacuated by a vacuum tube sealing machine to reduce the air pressure in the quartz tube to 10 -4 Pa, and then use the hydrogen-oxygen machine to seal the tube; put the quartz tube into the tube furnace and heat it at 5℃·min -1 The heating rate was increased to 450°C and calcined for 1 h to obtain a copper single atom catalyst with a mass content of 15 wt% supported on a polymer carbon nitride substrate.

[0029] Example 3 The nitrogen-containing precursor is calcined to obtain a carrier polymer carbon nitride; wherein the nitrogen-containing precursor is dicyandiamide. The calcination is divided into multiple steps, and the first step is calcined at a temperature of 550°C, for 2 hours, and at a heating rate of 2.3°C·min -1 The second step calcination temperature is 500℃, the time is 5h, and the heating rate is 5℃·min -1Repeat the second step of calcination three times until the polymer carbon nitride turns white.

[0030] 0.0326 g of 1,5-cyclooctadiene copper chloride dimer and 30 mL of anhydrous ethanol were placed in a 150 mL eggplant-shaped bottle, and mixed by ultrasonication for 10 min. Then, 0.0500 g of polymer carbon nitride carrier was added, and ultrasonication was performed for 20 min to obtain a mixed liquid. The mixed liquid was rotary evaporated at a rotary evaporation temperature of 50° C. and a rotation speed of 130 rpm to obtain a powder. The obtained powder was placed in the raw material end at the bottom of a single-ended quartz tube, and the air was evacuated by a vacuum tube sealing machine to reduce the air pressure in the quartz tube to 10 -4 Pa, and then use the hydrogen-oxygen machine to seal the tube; put the quartz tube into the tube furnace and heat it at 5℃·min -1 The heating rate was increased to 450°C and calcined for 1 hour to prepare a copper single atom catalyst with a mass content of 20wt% supported on a polymer carbon nitride substrate.

[0031] Example 4 The nitrogen-containing precursor is calcined to obtain a carrier polymer carbon nitride; wherein the nitrogen-containing precursor is dicyandiamide. The calcination is divided into multiple steps, and the first step is calcined at a temperature of 550°C, for 2 hours, and at a heating rate of 2.3°C·min -1 The second step calcination temperature is 500℃, the time is 5h, and the heating rate is 5℃·min -1 Repeat the second step of calcination three times until the polymer carbon nitride turns white.

[0032] 0.0408 g of 1,5-cyclooctadiene copper chloride dimer and 30 mL of anhydrous ethanol were placed in a 150 mL eggplant-shaped bottle, and mixed by ultrasonication for 10 min. Then, 0.0500 g of polymer carbon nitride carrier was added, and ultrasonication was performed for 20 min to obtain a mixed liquid. The mixed liquid was rotary evaporated at a rotary evaporation temperature of 50° C. and a rotation speed of 130 rpm to obtain a powder. The obtained powder was placed in the raw material end at the bottom of a single-ended quartz tube, and the air pressure in the quartz tube was reduced to 10 by a vacuum tube sealing machine. -4 Pa, and then use the hydrogen-oxygen machine to seal the tube; put the quartz tube into the tube furnace and heat it at 5℃·min -1 The heating rate was increased to 450°C and calcined for 1 hour to prepare a copper single atom catalyst with a mass content of 25wt% supported on a polymer carbon nitride substrate.

[0033] Example 5 The nitrogen-containing precursor is calcined to obtain a carrier polymer carbon nitride; wherein the nitrogen-containing precursor is dicyandiamide. The calcination is divided into multiple steps, and the first step is calcined at a temperature of 550°C, for 2 hours, and at a heating rate of 2.3°C·min -1 The second step calcination temperature is 500℃, the time is 5h, and the heating rate is 5℃·min -1Repeat the second step of calcination three times until the polymer carbon nitride turns white.

[0034] 0.0571 g of 1,5-cyclooctadiene copper chloride dimer and 30 mL of anhydrous ethanol were placed in a 150 mL eggplant-shaped bottle, and mixed by ultrasonication for 10 min. Then, 0.0500 g of polymer carbon nitride carrier was added, and ultrasonication was performed for 20 min to obtain a mixed liquid. The mixed liquid was rotary evaporated at a rotary evaporation temperature of 50° C. and a rotation speed of 130 rpm to obtain a powder. The obtained powder was placed in the raw material end at the bottom of a single-ended quartz tube, and the air pressure in the quartz tube was reduced to 10 by a vacuum tube sealing machine. -4 Pa, and then use the hydrogen-oxygen machine to seal the tube; put the quartz tube into the tube furnace and heat it at 5℃·min -1 The heating rate was increased to 450°C and calcined for 1 h to obtain a copper single atom catalyst with a mass content of 35 wt% supported on a polymer carbon nitride substrate.

[0035] Example 6 The nitrogen-containing precursor is calcined to obtain a carrier polymer carbon nitride; wherein the nitrogen-containing precursor is dicyandiamide. The calcination is divided into multiple steps, and the first step is calcined at a temperature of 555°C, for 2 hours, and at a heating rate of 3°C·min -1 The second step calcination temperature is 505℃, the time is 6h, and the heating rate is 5℃·min -1 Repeat the second step of calcination three times until the polymer carbon nitride turns white. After multiple calcinations, the polymer carbon nitride support can be transformed from a block to a nanosheet by simple thermal stripping, increasing the specific surface area of ​​the catalyst and providing more sites for loading metals.

[0036] 0.0082 g of 1,5-cyclooctadiene copper chloride dimer and 30 mL of anhydrous ethanol were placed in a 150 mL eggplant-shaped bottle, and mixed by ultrasonication for 10 min. Then, 0.0500 g of polymer carbon nitride carrier was added, and ultrasonication was performed for 30 min to obtain a mixed liquid. The mixed liquid was rotary evaporated at a rotary evaporation temperature of 50° C. and a rotation speed of 130 rpm to obtain a powder. The obtained powder was placed in the raw material end at the bottom of a single-ended quartz tube, and the air was evacuated by a vacuum tube sealing machine to reduce the air pressure in the quartz tube to 10 -4 Pa, and then use the hydrogen-oxygen machine to seal the tube; put the quartz tube into the tube furnace and heat it at 5℃·min -1 The heating rate was increased to 450°C and calcined for 1 h to prepare the copper single atom catalyst.

[0037] Example 7 The nitrogen-containing precursor is calcined to obtain a carrier polymer carbon nitride, wherein the nitrogen-containing precursor is melamine. The calcination is divided into multiple steps, the first step of which is calcined at a temperature of 560°C, for 1 hour, and at a heating rate of 1°C·min -1The second step calcination temperature is 510℃, the time is 5h, and the heating rate is 4℃·min -1 Repeat the second step of calcination 4 times until the polymer carbon nitride turns white. After multiple calcinations, the polymer carbon nitride support can be transformed from block to nanosheet by simple thermal stripping, increasing the specific surface area of ​​the catalyst and providing more sites for loading metals.

[0038] 0.0082 g of 1,5-cyclooctadiene copper chloride dimer and 30 mL of anhydrous ethanol were placed in a 150 mL eggplant-shaped bottle, and mixed by ultrasonication for 10 min. Then, 0.0500 g of polymer carbon nitride carrier was added, and ultrasonication was performed for 20 min to obtain a mixed liquid. The mixed liquid was rotary evaporated at a rotary evaporation temperature of 50° C. and a rotation speed of 130 rpm to obtain a powder. The obtained powder was placed in the raw material end at the bottom of a single-ended quartz tube, and the air pressure in the quartz tube was reduced to 10 by a vacuum tube sealing machine. -4 Pa, and then use the hydrogen-oxygen machine to seal the tube; put the quartz tube into the tube furnace and heat it at 5℃·min -1 The heating rate was increased to 460°C and calcined for 1 h to prepare the copper single atom catalyst.

[0039] Example 8 The nitrogen-containing precursor is calcined to obtain a carrier polymer carbon nitride; wherein the nitrogen-containing precursor is dicyandiamide. The calcination is divided into multiple steps, and the first step is calcined at a temperature of 550°C, for 3 hours, and at a heating rate of 2°C·min -1 The second step calcination temperature is 500℃, the time is 7h, and the heating rate is 6℃·min -1 Repeat the second step of calcination three times until the polymer carbon nitride turns white. After multiple calcinations, the polymer carbon nitride support can be transformed from a block to a nanosheet by simple thermal stripping, increasing the specific surface area of ​​the catalyst and providing more sites for loading metals.

[0040] 0.0082 g of copper chloride and 30 mL of anhydrous ethanol were placed in a 150 mL eggplant-shaped bottle, and the mixture was fully ultrasonicated for 10 min. Then, 0.0500 g of polymer carbon nitride carrier was added, and the mixture was fully ultrasonicated for 20 min to obtain a mixed liquid. The mixed liquid was rotary evaporated at a rotary evaporation temperature of 50 ° C and a rotation speed of 130 rpm to obtain a powder. The obtained powder was placed in the raw material end at the bottom of a single-ended quartz tube, and the air was evacuated by a vacuum tube sealing machine to reduce the air pressure in the quartz tube to 10 -4 Pa, and then use the hydrogen-oxygen machine to seal the tube; put the quartz tube into the tube furnace and heat it at 5℃·min -1 The heating rate was increased to 455°C and calcined for 2 hours to prepare the copper single atom catalyst.

[0041] Characterization of Examples 1-5: See also Figure 1 and Figure 2No Cu-related nanoparticles were detected or observed in the XRD spectra and TEM images. The AC-STEM images further proved the formation of Cu single atoms, which were uniformly dispersed in the support.

[0042] See also Figure 4 It can be seen that Example 3 has the best catalytic activity, and the high-loaded single-atom catalyst has practical significance.

[0043] Application experiment: The electrochemical performance test of the present invention was carried out on a CHI 760e (Shanghai Chenhua Instrument Co., Ltd.) electrochemical workstation. The pure acetylene activity test used a flow cell as an electrolytic cell and C2H2 (99.999%) gas as a reaction gas. 1 mol·L -1 KOH was used as the electrolyte, and an anion membrane was used to separate the cathode chamber and the anode chamber. Hg / HgO and nickel foam were used as the reference electrode and the counter electrode, respectively. The impurity removal test of crude ethylene gas flow containing acetylene impurities used a membrane electrode (MEA) as the electrolytic cell and a crude ethylene mixed gas (0.5% C2H2, 20% C2H4, Ar filling) as the reaction gas, 1 mol·L -1 KOH is used as the electrolyte, an anion membrane is used to separate the cathode chamber and the anode chamber, and nickel foam is used as the counter electrode. The preparation method of the working electrode is as follows: 3 mg of the catalyst prepared in Example 3 was evenly dispersed in a mixture of isopropanol (600 μL) and 5% nafion solution (4 μL), and ultrasonicated for 30 minutes; then 200 μL of the catalyst ink was sprayed on YLS30T carbon paper with a gas diffusion layer (1×1 cm) using an air brush, and after natural drying, a working electrode loaded with a copper single atom catalyst was obtained.

[0044] The gas flow rate in the specific test was controlled by a mass flow meter. The test was conducted in continuous constant current mode, and the product content was detected by a gas chromatograph. The FID detector was used to detect C2H2, C2H4, C2H6 and butadiene, and the TCD detector was used to detect H2.

[0045] See also Figure 5 It can be seen that the catalyst can efficiently produce ethylene while suppressing the formation of C4 products (Faraday efficiency <0.5%).

[0046] Table 1 is the ICP test data of copper single atoms prepared in Examples 1-5

[0047] The present invention describes in detail the preparation method of the catalyst and its practical effect in applications such as preparing ethylene by hydrogenation of acetylene and removing impurities from acetylene in ethylene-acetylene mixed gas. The present invention can obtain an ultra-high-load supported copper single-atom catalyst, which can better meet the needs of practical applications, and the method has a wide range of raw material sources and is easy to implement.

[0048] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing an ultra-high loading supported copper single atom catalyst, characterized in that: The following steps are involved: calcining the nitrogen-containing precursor to obtain polymer carbon nitride; Adding polymer carbon nitride to an ethanol dispersion of a copper precursor, ultrasonicating to obtain a mixed liquid, and evaporating to obtain a powder; The powder is calcined under vacuum to obtain a high-load supported copper single-atom catalyst.

2. The method for preparing the ultra-high loading supported copper single atom catalyst according to claim 1, characterized in that: The nitrogen-containing precursor is dicyandiamide or melamine.

3. The method for preparing the ultra-high loading supported copper single atom catalyst according to claim 1, characterized in that: The conditions for calcining the nitrogen-containing precursor are: first calcining at 550-560° C. for 1-3 hours, then calcining at 500-510° C. for 5-7 hours, and repeating calcining at 500-510° C. for 5-7 hours 3-4 times.

4. The method for preparing the ultra-high loading supported copper single atom catalyst according to claim 3, characterized in that: 1-3℃·min -1 The heating rate is 4-6℃·min -1 The heating rate is increased to 500-510°C.

5. The method for preparing the ultra-high loading supported copper single atom catalyst according to claim 3, characterized in that: The mass ratio of polymer carbon nitride to copper precursor is 0.05:0.0082-0.0571.

6. The method for preparing the ultra-high loading supported copper single atom catalyst according to claim 1, characterized in that: The copper precursor is 1,5-cyclooctadiene copper chloride dimer or copper chloride.

7. The method for preparing the ultra-high loading supported copper single atom catalyst according to claim 1, characterized in that: The powder is calcined under vacuum at a temperature of 450-460° C. for 1-2 hours.

8. The method for preparing the ultra-high loading supported copper single atom catalyst according to claim 7, characterized in that: At 5℃·min -1 The heating rate is increased to 450-460°C.

9. An ultra-high loading supported copper single atom catalyst prepared according to the method according to any one of claims 1 to 8.

10. Use of an ultra-high loading supported copper single atom catalyst prepared by the method according to any one of claims 1 to 8 in an electrocatalytic acetylene reduction reaction.

Citation Information

Patent Citations

  • Nitrogen self-doped graphitizing carbon nitride nanosheet photocatalyst as well as preparation method and application thereof

    CN108325555A

  • Method for improving selectivity of hydrogenation reaction to generate intermediate product

    CN116003203A

  • Copper monatomic catalyst with high loading capacity and thermal stability as well as preparation method and application of copper monatomic catalyst

    CN117839710A

  • Efficient synthesis method of high-loading-capacity monatomic catalyst

    CN118437411A

  • Alloy type catalyst as well as preparation method and application thereof

    CN118616076A